LEARNING MOTIVATION AND SELF-ESTEEM: A CORRELATIONAL STUDY AMONG STUDENTS IN THE GUIDANCE AND COUNSELING - Nasution, Salsabila; Ardis, Nurfaidah (Jurnal Kopendik, 2026)
Self-esteem and academic motivation are two psychological aspects that play a crucial role in supporting students’ academic success. This study aims to examine the relationship between academic motivation and self-esteem among Guidance and Counseling students. The study employed a quantitative correlational approach involving 305 students as the sample. The instruments used were the learning motivation scale by Bin Dayel and the State Self-Esteem Scale by Heatherton. Validity and reliability tests were conducted on 45 students outside the sample. Data analysis utilized Kendall’s Tau-b correlation test because the data did not meet the assumption of normality. The results indicate a significant positive relationship between learning motivation and self-esteem (τ = 0.274; p < 0.001; effect size = 0.281). These findings suggest that self-esteem is a psychological factor that should be considered in efforts to enhance students’ learning motivation. These findings imply the importance of strengthening the self-esteem of Guidance and Counseling students as a means of enhancing their learning motivation. These results can serve as a foundation for university lecturers and counselors in designing interventions that support the development of students’ self-esteem. Future research is recommended to include other psychological variables and employ more diverse methods to strengthen the findings obtained.